Rich crime, poor crime : inequality and the rule of law - Webster, Colin (Emerald Publishing Limited, 2023)
In 21st century Britain the rich are protected while the poor punished. Rich Crime, Poor Crime shows how contemporary British society is founded on a legacy of past plunder and dispossession by elites against the rest. Over centuries, power and property have been consolidated in the hands of a few and coded in legal systems that favoured the rich and created extreme inequality. Colin Webster puts a spotlight on Britain's hereditary and new ruling classes, whose inherited entanglements in land ownership, war and conquest, new world slavery, finance, trade, industry and empire allow them to accumulate and grow capital and wealth at the expense of others. He reveals a system facilitated by political corruption and wealth that accommodates serious wrongdoing - such as corporate, banking and accounting fraud, money laundering and tax evasion - and does substantial harm to fellow Britons. Examining the conditions of extreme inequality that give rise to poor crime and rich crime - and to the social response to both types of crime - we find them to be deeply implicated one with the other. Rich Crime, Poor Crime is vital reading for academics and professionals interested in the fields of history, sociology, criminology, and politics.